1992
DOI: 10.1177/000348949210100601
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinthine Enhancement on Gadolinium-Enhanced Magnetic Resonance Imaging in Sudden Deafness and Vertigo: Correlation with Audiologic and Electronystagmographic Studies

Abstract: Sudden deafness with or without vertigo presents a difficult diagnostic problem. This article describes 12 patients with enhancement of the cochlea and/or vestibule on gadolinium-diethylenetriamine pentaacetic acid-enhanced magnetic resonance imaging (MRI), correlating the enhancement with the auditory and vestibular function. All patients were studied with T2-weighted axial images taken through the whole brain, enhanced 3-mm axial T1-weighted images taken through the temporal bone, and enhanced T1-weighted sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
2
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 5 publications
1
46
2
1
Order By: Relevance
“…However, Mark AS et al reported in their study that pathologies with central origin were found in some cases in which MRI was not required. 11 In our study, MRI of 6 out of 33 patients with peripheral vestibulopathy revealed a central lesion associated with vertigo. Although the difference between pathologies identified with MRI and abnormal audiovestibular tests was not significant, there was clinical significance.…”
Section: Discussionsupporting
confidence: 49%
“…However, Mark AS et al reported in their study that pathologies with central origin were found in some cases in which MRI was not required. 11 In our study, MRI of 6 out of 33 patients with peripheral vestibulopathy revealed a central lesion associated with vertigo. Although the difference between pathologies identified with MRI and abnormal audiovestibular tests was not significant, there was clinical significance.…”
Section: Discussionsupporting
confidence: 49%
“…Following resolution of hearing loss in two of 12 patients with initial enhancement in the cochlea or labyrinth, the inner ear enhancement on MRI was lost (Mark et al, 1992). Animal experiments have given further support to a viral etiology for idiopathic SSNHL.…”
Section: Theories Of the Etiology Of Idiopathic Ssnhlmentioning
confidence: 93%
“…14 Since Mark et al 23 reported asymmetric labyrinthine enhancement after IV contrast in patients with sudden deafness and vertigo, continued technologic advances have improved our ability to resolve the delicate structures of the inner ear. Different methods have been used to assess the membranous labyrinth, with inherent variations among scanner vendors, protocols, coils, and contrast agents.…”
Section: Discussionmentioning
confidence: 99%